Pemberdayaan Pemerintah Desa Di Kecamatan Lantari Jaya Kabupaten Bombana - Tompo, Tompo (IAIN Palopo, 2019)
Rural development plays an important role in the context of national development. Besides of it covers most of the territory of the Unitary State of the Republic of Indonesia, also about seventy percent of Indonesia's population living in rural areas. For that reason, Rural Community Development requires continuous efforts, because it has important role in strengthening national endurance. If it?s measured by economic and social indicators, in general most of the existing Village welfare level is still relatively low. As can be seen in rural areas until now, where there are still many development imbalances between rural and urban. And the most important role to activate the wheels of development in rural areas is the village government through empowerment and society participation. Keywords: Empowerment, Village Government, Social Welfare